Pennsylvania Sentencing Data, 1996 ([Verlag nicht ermittelbar], 2000)
The Pennsylvania Commission on Sentencing is a legislative agency of the Commonwealth of Pennsylvania. The Commission develops sentencing guidelines for judges to use when sentencing felony and misdemeanor offenses. The judges report sentences to the Commission on a Guideline Sentence Form. This data collection reflects all felonies and misdemeanors reported to the Commission that were sentenced during calendar year 1996. The data are contained in two files. Part 1, Records Data, provides information on each offender, including rudimentary demographic characteristics and prior offense history. Part 2, Offense Data, contains information on each offense, including the statutory citation for the offense, the Offense Gravity Score assigned by the Commission, the offender's Prior Record Score, and the sentence given the offender.